EU Rights Project data collection - O'Brien, Charlotte (UK Data Service, 2018)
The EU Rights Project was a legal action research project - in which the lead researcher had a dual role, of both advising EU nationals in the UK on their welfare rights, and doing case work and advocacy on their behalf, and secondly, documenting the obstacles encountered, through field notes. The project was supported through focus groups and interviews, to help shape the research questions, and ask about the project's findings, so some of the data are transcriptions of those interactions. The bulk of the work, and so the bulk of the data, however, relates to the legal action case work. The data relates to 41 separate client cases on which I worked, featuring clients from 15 Member States; of these three of these (case 1, case and case 38) each gave rise to a further case, due to different enquiries from the same client. I also received nine evidence submissions: that is, pre-prepared case studies that did not require my input. This comes to a total of 53 cases, or sets of notes. The main research questions, to which the field notes were intended to speak were: (i) what are the key legal and administrative obstacles to EU nationals making benefit claims in the UK? (ii) what are the key legal and administrative obstacles to EU nationals challenging benefit decisions - at first instance/on mandatory consideration/on appeal/in tribunal in the UK? and (iii) how many contacts, and of what type, do clients have to make/receive during the course of their cases? The project investigates at first-hand how easy it is to use the rights granted by EU law in the UK, to test how well EU citizenship rights work in practice, and to test the values of social and administrative justice in EU law. In collaboration with Ripon Citizens Advice Bureau, the Principal Investigator (PI) will set up a specialist advice and advocacy service on EU welfare claims. While advising and representing clients, the PI will also conduct a parallel study of the obstacles the clients encounter during their claims and appeals. This 'advice led ethnography' is an innovative new approach, especially in the context of EU law. It combines socio-legal studies with theoretical, philosophical and historical work on EU social law.